Pemberdayaan Kelompok Budidaya Ikan Melalui Pembuatan Pakan Ikan Gabus Bernilai Ekonomis - Rosalina Edy Swandayani; Arista Suci Andini; Hasan Basri; Alvin Juniawan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to encourage fish farming groups by making snakehead fish feed that has economic value. The method of implementing this service was through socialization and training. The partners in community service activities were the Mina Jaya Abadi Fish Cultivation Group (Pokdakan) in Peresak Village West Lombok Regency. The evaluation was carried out by giving a pretest and posttest, which then been analyzed descriptively. The results of this community service activity were increasing the understanding and skills of partners regarding the use of yards, nutrition, and content of snakehead fish, and how to cultivate and make snakehead fish feed. In addition, partners also understood the opportunities for Snakehead fish for post-Covid-19 entrepreneurs. Based on the results of the activities that have been carried out, the PkM team also assisted with tools for making fish feed which could reduce production costs for buying commercial fish feed and use alternative feeds.